TOURISTS’ EMOTIONAL EXPERIENCES AT TOURISM DESTINATIONS: ANALYSIS OF SOCIAL MEDIA REVIEWS (Journal of Event, Tourism and Hospitality Studies, 2021)
Experiential aspect of consumption has becoming more important in the era of social media. Social life has changed. Today, people are exposed to overflowing information; voluntarily or involuntarily. Almost everyone can express their emotional experience about tourism destinations, which may influence viewers’ response and their purchasing decision. Thus, this study was conducted to identify the salient domains of emotional experiences remembered and recalled by tourists in the online social environments. Content analysis method was utilized to uncover the common themes from 200 online reviews about tourism destinations in Malaysia. The study revealed the presence of cognitive and affective components in online reviews. It also discovered that tourists attributed their emotional experience to concrete factors, which include core (activities) and facilitating components (accommodation, food and beverages and transportation). This in-depth analysis of unstructured text reviews captured some clues about tourists’ emotional experience that would help tourism providers in developing strategies that can stimulates desired emotion, improve positive electronic word of mouth (eWOM) transmissions, which later may contribute to building a destination brand that resonates with its consumers.